Editorial: the internet and the EU market. Issue 2 (2nd April 2020) - Fickers, Andreas; Schafer, Valérie
Abstract: This special issue is the result of an open call launched two years ago in connection with the activities of the Robert Schuman Initiative, led at the University of Luxembourg by Prof. David Howarth. Our call for papers invited scholars to historically analyse the relationship between the EU single market and the internet from a critical perspective.  This interdisciplinary issue mainly analyses how the development of the Internet has created major regulatory challenges at the EU level. It looks at the various stakeholders and their changing roles, the regulatory framework and its turning points, underlining policy changes but also strong legacies and continuities within EU policies and debates.